Quantum Dot-Based Nanosensors for In Vitro Detection of Mycobacterium tuberculosis - Viktor V. Nikolaev; Tatiana B. Lepekhina; Alexander S. Alliluev; Elham Bidram; Pavel M. Sokolov; Igor R. Nabiev; Yury V. Kistenev (Nanomaterials)
Despite the existing effective treatment methods, tuberculosis (TB) is the second most deadly infectious disease, its carriers in the latent and active phases accounting for more than 20% of the world population. An effective method for controlling TB and reducing TB mortality is regular population screening aimed at diagnosing the latent form of TB and taking preventive and curative measures. Numerous methods allow diagnosing TB by directly detecting Mycobacterium tuberculosis (M.tb) biomarkers, including M.tb DNA, proteins, and specific metabolites or antibodies produced by the host immune system in response to M.tb. PCR, ELISA, immunofluorescence and immunochemical analyses, flow cytometry, and other methods allow the detection of M.tb biomarkers or the host immune response to M.tb by recording the optical signal from fluorescent or colorimetric dyes that are components of the diagnostic systems. Current research in biosensors is aimed at increasing the sensitivity of detection, a promising approach being the use of fluorescent quantum dots as brighter and more photostable optical tags. Here, we review current methods for the detection of M.tb biomarkers using quantum dot-based nanosensors and summarize data on the M.tb biomarkers whose detection can be made considerably more sensitive by using these sensors.